The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/2015gl066156
|View full text |Cite
|
Sign up to set email alerts
|

Surface water‐groundwater connectivity in deltaic distributary channel networks

Abstract: Delta distributary channel networks increase river water contact with sediments and provide the final opportunity to process nutrients and other solutes before river water discharges to the ocean. In order to understand surface water‐groundwater interactions at the scale of the distributary channel network, we created three numerical deltas that ranged in composition from silt to sand using Delft3D, a morphodynamic flow and sediment transport model. We then linked models of mean annual river discharge to stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 80 publications
0
32
0
Order By: Relevance
“…Finally, we want to emphasize the broad applicability of this framework to diverse fields in the geosciences where multiprocess multiscale interactions dictate the overall system behavior. Examples include flux transport taking into account surface-subsurface exchange (Sawyer et al, 2015), integrated wetland and river systems (Hansen et al, 2018), interaction types among species in ecological systems (Pilosof et al, 2017), and climate networks (Donges et al, 2011).…”
Section: 1029/2018gl078355mentioning
confidence: 99%
“…Finally, we want to emphasize the broad applicability of this framework to diverse fields in the geosciences where multiprocess multiscale interactions dictate the overall system behavior. Examples include flux transport taking into account surface-subsurface exchange (Sawyer et al, 2015), integrated wetland and river systems (Hansen et al, 2018), interaction types among species in ecological systems (Pilosof et al, 2017), and climate networks (Donges et al, 2011).…”
Section: 1029/2018gl078355mentioning
confidence: 99%
“…However, in systems subject to flow direction reversal across the boundary (e.g., due to a flood tide), the total time a water parcel spends in the domain can be underestimated by the residence time (Monsen et al, ), leading to the adoption of the exposure time, or the cumulative amount of time a water parcel spends in the control volume regardless of its excursions outside the domain (e.g., de Brauwere et al, ; de Brye et al, ; Delhez, ; Monsen et al, ; Viero & Defina, ). Despite the environmental importance of river deltas, the study of water transport time scales in coastal river deltas is relatively nascent (Hiatt & Passalacqua, ; Sawyer et al, ; Sendrowski & Passalacqua, ). The goal of this paper is to quantify controls on the exposure time distribution (ETD) in a coastal river delta.…”
Section: Introductionmentioning
confidence: 99%
“…Sawyer et al . [] found that mesoscale landforms are one of the major controlling factors in surface water‐groundwater exchange and solute retention. Macrotopography refers to the overall topographic gradient.…”
Section: Introductionmentioning
confidence: 99%